Optimizing Productive Zakat for Economic Empowerment: Evidence from BAZNAS Microfinance Models - Sari Damayanti; Moh. Najib; Sri Dewi Anggadini; Deni Permana (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
Economic empowerment through zakat has become increasingly important to reduce poverty and promote social welfare in muslim communities. This study aims to analyze the optimization of productive zakat as an instrument for empowering the Muslim community’s economy through the paradigm transformation from consumptive zakat to productive zakat, using BAZNAS Microfinance as a case study. A qualitative-normative approach was employed, combining theological and empirical analyses. Data were collected through in-depth interviews, observations, and literature review, focusing on three BAZNAS microfinance models: village, mosque, and religious study group. Thematic interpretation (tafsir maudhū’i) of Qur’anic verses and hadiths on zakat was conducted, considering asbābun nuzūl, asbābul wurūd, mufrad and ijmaly meanings, and munasabah to reveal the normative dimension of Islamic economic empowerment. Findings show that productive zakat significantly fosters mustahik economic independence through sharia-based microfinance, entrepreneurship training, and ongoing mentoring. Although the effectiveness of each model varies with social context and institutional support, all contribute positively to improving recipients’ welfare. The study concludes that optimizing productive zakat is both an economic strategy and a fulfillment of maqāṣid al-syarī’ah, particularly in preserving wealth (hifzh al-māl) and promoting public welfare (maslahah ‘ammah).